2005
DOI: 10.1086/423192
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray Study of Herbig Ae/Be Stars

Abstract: We present ASCA results of intermediate-mass pre-main-sequence ( PMS) stars, or Herbig Ae/Be (HAeBe) stars. Among the 35 ASCA pointed sources, we detect 11 plausible X-ray counterparts. X-ray luminosities of the detected sources in the 0.5-10 keV band are in the range of log L X $ 30 32 ergs s À1 , which is systematically higher than those of low-mass PMS stars. This fact suggests that the contribution of a possible low-mass companion is not large. Most of the bright sources show significant time variation; in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
132
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(142 citation statements)
references
References 69 publications
10
132
0
Order By: Relevance
“…These data were presented previously by Hamaguchi et al (2000Hamaguchi et al ( , 2005. Here we only discuss the ∼6 h observing sequence 21007010, during which the decay phase of an X-ray flare was observed.…”
Section: Coronographic Adaptive Opticsmentioning
confidence: 69%
“…These data were presented previously by Hamaguchi et al (2000Hamaguchi et al ( , 2005. Here we only discuss the ∼6 h observing sequence 21007010, during which the decay phase of an X-ray flare was observed.…”
Section: Coronographic Adaptive Opticsmentioning
confidence: 69%
“…Siebenmorgen et al (1998) reported the presence of a large circumstellar elliptical ring of PAH emission with thousands of AU in diameter and an indication for the possible existence of a candidate companion. It was also detected as an X-ray source in ROSAT and Chandra observations (Hamaguchi et al 2005;Stelzer et al 2006) HD 139614: Our previous measurements of HD 139614 revealed the presence of a weak magnetic field in the range from −116 G to −450 G. (Hubrig et al 2004b;. The current diagnosis of magnetic fields in this star yielded no detection at a 3σ level, neither in Balmer nor in metal lines, with error bars as low as 25 G. In analogy with our previous detections, the measured magnetic field is of negative polarity and Ca ii H&K lines in HD 139614 show distinct Zeeman features.…”
Section: Stars With Measurements Suggestivementioning
confidence: 96%
“…Damiani et al 1994;Zinnecker & Preibisch 1994;Hamaguchi et al 2005;Stelzer et al 2009). Then, to further restrict the range of masses, and that of absorptions, we excluded stars with I c > 16, corresponding to M > 0.1−0.2 M for COUP sources with low optical absorption 4 (A V < 2.0).…”
Section: Sample Definitions and Selection Criteriamentioning
confidence: 99%